A student team project in real context: The team view - Ribeiro, Francisca (2016)
In the Industrial Engineering and Management Integrated Master course the projects in real industrial context are assumed to play a crucial role in the development of key technical and professional skills in students. In the 7 th semester of this integrated master course the students are involved in a large real context project integrating many different subjects covered in 5 different curricular units. Student teams must analyze and diagnose a production unit in a company, identify improving opportunities, design solutions and implement them if possible. These experiences are very demanding to students since many different uncontrollable variables are influencing their performance as team and as individuals. In this article the students will describe the experience from different perspectives, such as: personal interaction, group and project management, technical challenges, communication issues, as well as the challenges in meeting teachers and company staff expectations.